Οι Venethi στα Getica του Ιορδάνη: πρόγονοι των Σλάβων; - Καρδαράς Γεώργιος Θεόδωρος (Tekmeria, 2015)
Regarding the question of the ethnogenesis and the cradle of the Slavs, the paper considers the information on the ‘‘forgotten’’ people of Venethi in Jordanes’ Getica, dated in the mid-sixth century A. D., The critical approach of Jordanes’ testimonies, the examination of references on the Venethi from ancient authors as Plinius the Elder, Tacitus and Ptolemaios, sources placing the Venethi/Venedi in the area of river Vistula, and the geographical location of the people in Tabula Peutingeriana is attempted. Moreover, the paper tackles the views of some scholars on the correlation of the Venethi-ancestors of the Early Slavs (Sclaveni and Antes) with ancient tribes mentioned by Ptolemaios (Stavanoi, Suovinoi) and Herodotus (Neuroi, Budinoi) in their attempt to establish a continuity between these tribes and the Early Slavs. Reference is made also to historiographical approaches on the Venethi question from the ‘‘romantic’’ historians of the nineteenth century up to today, as well as the importance of the Venethi and certain ancient cultures on the development of national historiography in Slavic countries. The connection of Venethi with the Early Slavs is rejected, taking into account the plausible placement of Venethi in Lower Vistula and Baltic Sea area and, on the other hand, the appearance of the early Slavic cultures, namely Koločin, Korčak and Pen’kovka, in the area of modern Russia, Ukraine and Belarus.